Health impact metrics for air pollution management strategies. (December 2015) - Martenies, Sheena E.; Wilkins, Donele; Batterman, Stuart A.
ABSTRACT: Health impact assessments (HIAs) inform policy and decision making by providing information regarding future health concerns, and quantitative HIAs now are being used for local and urban-scale projects. HIA results can be expressed using a variety of metrics that differ in meaningful ways, and guidance is lacking with respect to best practices for the development and use of HIA metrics. This study reviews HIA metrics pertaining to air quality management and presents evaluative criteria for their selection and use. These are illustrated in a case study where PM2.5 concentrations are lowered from 10 to 8 μg/m 3 in an urban area of 1.8 million people. Health impact functions are used to estimate the number of premature deaths, unscheduled hospitalizations and other morbidity outcomes. The most common metric in recent quantitative HIAs has been the number of cases of adverse outcomes avoided. Other metrics include time-based measures, e.g., disability-adjusted life years (DALYs), monetized impacts, functional-unit based measures, e.g., benefits per ton of emissions reduced, and other economic indicators, e.g., cost-benefit ratios. These metrics are evaluated by considering their comprehensiveness, the spatial and temporal resolution of the analysis, how equity considerations are facilitated, and the analysis and presentation of uncertainty. In the case study, the greatest number of avoided cases occurs for low severity morbidity outcomes, e.g., asthma exacerbations (n = 28, 000) and minor-restricted activity days (n = 37, 000); while DALYs and monetized impacts are driven by the severity, duration and value assigned to a relatively low number of premature deaths (n = 190 to 230 per year). The selection of appropriate metrics depends on the problem context and boundaries, the severity of impacts, and community values regarding health. The number of avoided cases provides an estimate of the number of people affected, and monetized impacts facilitate additional economic analyses useful to policy analysis. DALYs are commonly used as an aggregate measure of health impacts and can be used to compare impacts across studies. Benefits per ton metrics may be appropriate when changes in emissions rates can be estimated. To address community concerns and HIA objectives, a combination of metrics is suggested. Highlights: HIAs have used many metrics, including avoided cases, DALYs and monetized impacts. There is a need to identify appropriate metrics for use in urban-scale air pollution HIA. Metrics should be comprehensive, spatially and temporally resolved, and account for vulnerability. Metrics should evaluate and clearly present uncertainty. The use of multiple metrics is suggested to fully characterize the impacts of a proposed policy.